Online Writing Skills Training for Elementary School Teachers in the Klaten Region, Central Java - Budiyono, Sri; Widodo, Sudiyo; Warsito, Warsito; Haryono, Purwo; Pratomo, Sigit Adhi; Guntoro, Muhammad Yogi; Indrayanto, Bayu; Yuwono, Suhud Eko (PT Agung Media Publisher, 2025)
This community service program aimed to improve the writing skills of elementary school teachers in Klaten, Central Java, Indonesia. The training emphasized that writing is not merely arranging words, but also a process of conveying ideas, fostering understanding, and creating influence. The activity was conducted online (asynchronously) due to unfavorable weather conditions and the request of participants and partners. The training involved 25 participants and was implemented over two months, from February to March 2025. Each session was held every Sunday for 120 minutes. Learning materials were delivered through online lectures, practice exercises, and assignments. The program was implemented smoothly and in an orderly manner. Participants actively engaged in the sessions and completed all assignments. Evaluation results showed that all participants achieved satisfactory scores, reflecting an improvement in their understanding of writing skills. The online writing skills training successfully enhanced the competence of elementary school teachers in Klaten. Future programs may consider expanding participation beyond Klaten to reach a wider audience in need of writing skill development.